2020
DOI: 10.3390/pharmaceutics12090891
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Elemental Composition/Mobility and Skin Cell Proliferation of Fibrous Nanoclay/Spring Water Hydrogels

Abstract: Inorganic hydrogels formulated with spring waters and clay minerals are used to treat musculoskeletal disorders and skin affections. Their underlying mechanism of action for skin disorders is not clear, although it is usually ascribed to the chemical composition of the formulation. The aim of this study was to assess the composition and in vitro release of elements with potential wound healing effects from hydrogels prepared with two nanoclays and natural spring water. In vitro Franz cell studies were used and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 97 publications
(120 reference statements)
0
3
0
Order By: Relevance
“…Muco-/Bioadhesion to surfaces such as soft tissues enhances the potential of nanocomposite hydrogels as a wound dressing material due to the acquired surface roughness, attributed to the addition of clay minerals as well as the capacity to interlink with the irregularities of the surface. There have been many other clay-based nanocomposite hydrogels studied for wound healing applications [116] such as nanostructured hydrogel membranes based on chitosan biopolymer and MMT nanoparticles, with cytocompatibility, better cell morphology and attachment, and significant antibacterial activity [117]; attapulgitereinforced hydrogel membranes where the increase in clay contents showed antimicrobial activity against six tested pathogen strains and adequate hemolytic behavior compared to clay-free membranes [118]; fibrous nanoclay and spring water hydrogels accelerated wound healing with respect to the control [119] and released therapeutic agents with beneficial activity in wound healing [120]; agar/κ-carrageenan hydrogels reinforced with MMT exhibited antibiotic and analgesic effects presenting good antibacterial activity against E. coli and S. aureus [121]; laponite-reinforced gellan gum methacrylate (GG-MA) for the treatment of burn wounds using wound-dressing material with ofloxacin release [122]; and collagenbased hydrogels reinforced with different types of clays to determine their antimicrobial behavior, cellular viability, and gentamicin delivery profiles for skin regeneration [123]. [114] PVA Na-MMT Clay nanoparticles act as barriers against microbe penetration which enhances the protection against further wound infection and accelerates the wound healing process.…”
Section: Wound Healingmentioning
confidence: 99%
“…Muco-/Bioadhesion to surfaces such as soft tissues enhances the potential of nanocomposite hydrogels as a wound dressing material due to the acquired surface roughness, attributed to the addition of clay minerals as well as the capacity to interlink with the irregularities of the surface. There have been many other clay-based nanocomposite hydrogels studied for wound healing applications [116] such as nanostructured hydrogel membranes based on chitosan biopolymer and MMT nanoparticles, with cytocompatibility, better cell morphology and attachment, and significant antibacterial activity [117]; attapulgitereinforced hydrogel membranes where the increase in clay contents showed antimicrobial activity against six tested pathogen strains and adequate hemolytic behavior compared to clay-free membranes [118]; fibrous nanoclay and spring water hydrogels accelerated wound healing with respect to the control [119] and released therapeutic agents with beneficial activity in wound healing [120]; agar/κ-carrageenan hydrogels reinforced with MMT exhibited antibiotic and analgesic effects presenting good antibacterial activity against E. coli and S. aureus [121]; laponite-reinforced gellan gum methacrylate (GG-MA) for the treatment of burn wounds using wound-dressing material with ofloxacin release [122]; and collagenbased hydrogels reinforced with different types of clays to determine their antimicrobial behavior, cellular viability, and gentamicin delivery profiles for skin regeneration [123]. [114] PVA Na-MMT Clay nanoparticles act as barriers against microbe penetration which enhances the protection against further wound infection and accelerates the wound healing process.…”
Section: Wound Healingmentioning
confidence: 99%
“…Montmorillonite, laminar mineral, can be used to modify the release of drugs [29,42], and to protect them from the degradation [43]. Moreover, it have been recently demonstrated that clays have a proliferative effect on fibroblasts [44], which can lead to a potential synergistic effect between melatonin and montmorillonite for wound heling and skin protection.…”
Section: Introductionmentioning
confidence: 99%
“…The underlying mechanism of action for skin disorders of these formulations is usually ascribed to the chemical composition of the formulation. García-Villén et al [5] assessed the composition and in vitro release of elements with potential wound healing effects from hydrogels prepared with two nanoclays and natural spring water. In vitro Franz cell studies were used and the element concentration was measured by the Inductively Coupled Plasma technique.…”
mentioning
confidence: 99%